First myocardial infarctions in Asian and white men. - Hughes, L. O. (1989)
OBJECTIVE--To compare the presentation and natural course of first myocardial infarctions in immigrant Asians and the indigenous white population in Britain and the subsequent risk states of the two groups. DESIGN--Prospective ethnic comparison of consecutive patients with first myocardial infarctions. SETTING--Secondary referrals to a coronary care unit of a district general hospital. PATIENTS--128 Men (77 white, 54 Asian) presenting consecutively with a first myocardial infarction diagnosed on the basis of clinical, biochemical, and electrocardiographic findings. END POINT--Identification of mechanisms accounting for the increased rate of ischaemic heart disease in Asians. MEASUREMENTS AND MAIN RESULTS--Infarct size was assessed by measuring the release of creatine phosphokinase (all patients), radionuclide ventriculography (50), and contrast ventriculography (103). Risk states after infarction were assessed from the degree of ventricular dysfunction as determined by exercise electrocardiography (82 patients) and from the extent of coronary atheroma as determined by coronary arteriography (103). Glucose state was measured in fasting venous blood samples. Overall the relative rate of infarction was 4.9 times higher in Asians (95% confidence interval 3.4 to 6.9) than in the white population. Moreover, the relative rate of infarction was higher in Asians in all 10 year age groups, the greatest difference being in 30-39 year olds. The mean age of the Asian denominator population was 47.1 years compared with 49.5 years in the white population. Age at infarction was less in Asians (50.2 years) than in white patients (55.5 years; mean difference 5.5 years (95% confidence interval 2.5 to 7.1]. In Asians the mean creatine phosphokinase activity was 777 (95% confidence interval 155 to 1399) U/1 higher, radionuclide ejection fraction 8.9% (1.0% to 16.9%) lower, and left ventricular fractional shortening 4.8% (1.4% to 8.2%) lower than in white patients. The extent of coronary atheroma was significantly greater in Asians. The mean numbers of plaques in vessels not associated with infarction were 3.66 (median 3.0, range 0-10) in Asians compared with 1.97 (median 2.0, range 0-6) in white patients (p less than 0.001), and a higher proportion of Asians had three vessel coronary artery disease (p less than 0.001). Asians with diabetes or impaired glucose tolerance did not differ from those with normal blood glucose values. CONCLUSIONS--Atherogenesis arises earlier in Asians, contributing to premature first myocardial infarctions. The increased incidence of diabetes in Asians may not in itself be relevant in the greater propensity to coronary atheroma in Asians.